2022
DOI: 10.31744/einstein_journal/2022ao6896
|View full text |Cite
|
Sign up to set email alerts
|

Impact of blood levels of progesterone on the day of ovulation onset on clinical, laboratory and reproductive parameters of young patients undergoing assisted reproduction: a cross-sectional study

Abstract: Objective: To assess whether there is an association between the level of progesterone on the day of administration of human chorionic gonadotropin and clinical and laboratory characteristics, in addition to the results of in vitro fertilization of patients with a good prognosis. Methods: A cross-sectional study comprising 103 women who underwent intracytoplasmic sperm injection treatment, between November 2009 and May 2015, aged ≤35 years, with no comorbidities, with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In this study, we reported that UC decreased the level of PROG in females. PROG plays a vital role in maintaining normal reproductive function in females, and the lower PROG levels may contribute to the decline in reproductive function ( 49 ). Besides, our study identified that ER levels were reduced by CD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we reported that UC decreased the level of PROG in females. PROG plays a vital role in maintaining normal reproductive function in females, and the lower PROG levels may contribute to the decline in reproductive function ( 49 ). Besides, our study identified that ER levels were reduced by CD.…”
Section: Discussionmentioning
confidence: 99%